Critical Oculocardiac Reflex In Phacoemulsification: A Case Report - Prajakta Dandekar; Gautam Singh (Delhi Journal of Ophthalmology)
Critical Oculocardiac reflex (OCR) is very rare, especially during phacoemulsification, and we report one such case from our hospital. A 56-year-old male patient developed sudden bradycardia (pulse:38/min) and hypotension (BP:60/40mmHg) during phacoemulsification under topical anaesthesia. We terminated the surgery and managed the patient as a case of critical OCR with injection Atropine, IV fluids and inotropic drugs. Once the patient stabilised, we completed the remaining steps of the surgery successfully. Thus, life-threatening OCR can occur even in phacoemulsification and adhering to strict protocols with timely management can save a life.